Temporal map of the pig polytrauma plasma proteome with fluid resuscitation and intravenous vitamin C treatment. (25th August 2019) - Cudjoe, Emmanuel K.; Hassan, Zaneera H.; Kang, Le; Reynolds, Penny S.; Fisher, Bernard J.; McCarter, Jacquelyn; Sweeney, Christopher; Martin, Erika J.; Middleton, Paul; Ellenberg, Matthew; Fowler, Alpha A.; Spiess, Bruce D.; et al.
Abstract: Background: Fluid resuscitation plays a prominent role in stabilizing trauma patients with hemorrhagic shock yet there remains uncertainty with regard to optimal administration time, volume, and fluid composition (e.g., whole blood, component, colloids) leading to complications such as trauma‐induced coagulopathies (TIC), acidosis, and poor oxygen transport. Synthetic fluids in combination with antioxidants (e.g., vitamin C) may resolve some of these problems. Objectives: We applied quantitative mass spectrometry‐based proteomics [liquid chromatography‐mass spectrometry (LC‐MS/MS)] to map the effects of fluid resuscitation and intravenous vitamin C (VitC) in a pig model of polytrauma (hemorrhagic shock, tissue injury, liver reperfusion, hypothermia, and comminuted bone fracture). The goal was to determine the effects of VitC on plasma protein expression, with respect to changes associated with coagulation and trauma‐induced coagulopathy (TIC). Methods: Longitudinal blood samples were drawn from nine male Sinclair pigs at baseline, 2 h post trauma, and 0.25, 2, and 4 h post fluid resuscitation with 500 mL hydroxyethyl starch. Pigs were treated intravenously ( N  = 3/treatment group) with saline, 50 mg VitC/kg (Lo‐VitC), or 200 mg VitC/kg (Hi‐VitC) during fluid resuscitation. Results: A total of 436 plasma proteins were quantified of which 136 changed following trauma and resuscitation; 34 were associated with coagulation, complement cascade, and glycolysis. Unexpectedly, Lo‐VitC and Hi‐VitC treatments stabilized ADAMTS13 levels by ~4‐fold ( P  = .056) relative to saline and enhanced ADAMTS13/von Willebrand factor (VWF) cleavage efficiency based on LC‐MS/MS evidence for the semitryptic VWF cleavage product (VWF1275‐1286 ). Conclusions: This study provides the first comprehensive map of trauma‐induced changes to the plasma proteome, especially with respect to proteins driving the development of TIC.